Reddit as a “Safe Space” - Maria F. Grub (Weizenbaum Journal of the Digital Society)
This study explores the thematic landscape of depression, anxiety, and general mental health communities on Reddit, examining how users seek support within these online health communities (OHCs). Grounded in community theory, which frames OHCs as spaces for connection, shared identity, and collective learning (Wenger-Trayner & Wenger-Trayner, 2015), this research identifies unique and overlapping themes across 16 subreddits. The results show that all three communities address four main thematic categories (everyday life, dealing with the disease, diagnosis, and therapy) and prioritize emotional support over medical information-seeking. However, each community has a distinct focus: depression discussions revolve around negative self-reflection, anxiety communities emphasize active coping and stress relief, and broader mental health communities address diverse topics, including trauma. By highlighting OHCs’ dual role in providing emotional and informational support, this study advances health communication science, underscoring the therapeutic value of online spaces in reducing isolation and offering alternative support networks. Future research should examine interaction dynamics to improve the understanding of how OHCs contribute to positive coping strategies.